Explicit Learning of a Perceptual-Motor Skill after Stroke by Using Affected Hand - Iraj َAbdollahi; Mohammad Taghi Joghataei; Mahyar Salavati; Esmaeil Ebrahimi; Hossein A'shayeri (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: The aim of this research is study of explicit learning in unilateral stroke patients and comparison with normal individuals and identify effects of age, sex and study level in this motor learning. Materials & Methods: In this case-control analytical research we used a software for studying motor learning. In this software 4 squares with different colors were appeared on the monitor and individuals should press a defined key immediately after observing it. 15 patients and 15normal matched were participate in this research. In first day individuals practiced 8 motor block (4 regular blocks, then 2 blocks in randomed manner and finally 2 regular blocks). Next day individuals practiced a retention test consist of 2 regular block. Befor starting test, individuals took complete explanation about sequence of squares. All individuals were right handed and impaired hand in patients was right side and patients practiced with impaired hand. Motor sequences and blocks were recorded with software. Data was analyzed by using Chi-square test, T-test for independent groups and ANOVA. Results: This research revealed that performance of patients was slower than normal group (P0/05). Block times were decreased from second to fourth block and time differences between second block with eight and tenth block (next day) were significant in both patient and normal groups (P<0/05). Conclusion: Although performance of unilateral stroke patients was slower than normal individuals, motor learning (stable decrease of block times) was similar. On the other hand in patients with unilateral stroke ability of motor learning with affected hand was preserved.